Toxoplasma's ways of manipulating the host transcriptome via secreted effectors. (August 2015) - Hakimi, Mohamed-Ali; Bougdour, Alexandre
Highlights: Toxoplasma persists in the host by co-opting central hubs of immune pathways. The parasite takes over control of host cell transcriptome following invasion. Toxoplasma secretes a range of effectors in host cell through specialized organelles. Parasite-derived effectors selectively modulate host transcription factor activity. Abstract: The obligate intracellular parasite Toxoplasma gondii strikes a subtle balance with the host immune system that not only prevents host death but also promotes parasite persistence. Although being enclosed within a parasitophorous vacuole, the parasite actively interfaces with host cell signaling pathways, thereby directing host cell responses. To this end, T. gondii delivers effector proteins into the host cell that co-opt host transcription factors and eventually modulate gene expression. Aside from the secretory Rhoptry organelles initially described as the main source of such effectors, Dense Granules are now recognized as critical in delivering products that remain confined at the vacuolar space or traffic beyond the vacuole membrane to the host cell nucleus and contribute to rewire host gene expression. This review highlights the latest breakthroughs in T. gondii effector discovery and their modus operandi during infection.